Analisis Pengaruh Tax Haven Utilization, Thin Capitalization dan Intangible Assets terhadap Tax Avoidance dengan Transfer Pricing sebagai Variabel Mediasi - Olivia Alviolenta; Dedi Haryadi; Hartono Hartono (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
This study is aimed at exploring more deeply the impact of Tax Haven Utilization, Thin Capitalization, and Intangible Assets on Tax Avoidance as proxied by the Effective Tax Rate (ETR), as well as examining the role of Transfer Pricing as a mediating variable. The study is conducted based on data from energy sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period, totaling 230 observations selected using a purposive sampling method. Data processing is carried out using panel data regression with the Fixed Effect Model (FEM) and Common Effect Model (CEM) approaches using Stata 17, along with the Sobel mediation test. The results of the study show that Thin Capitalization has a negative and significant impact on Tax Avoidance, whereas Tax Haven Utilization and Intangible Assets have less influence. In addition, the three independent variables do not have a significant impact on Transfer Pricing, and Transfer Pricing also has little effect on Tax Avoidance. The results of the mediation test indicate that Transfer Pricing is not able to mediate the relationship between the independent variables and Tax Avoidance.